1998
DOI: 10.1039/a807248e
|View full text |Cite
|
Sign up to set email alerts
|

Iron-catalyzed allylic amination by nitroorganics

Abstract: CpFe(CO) 2 ] 2 catalyzes the reaction of nitroaromatics with olefins under CO to produce allyl amines regioselectively; a coordinated organonitrogen species is implicated as the active aminating agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Following our first report, Nicholas and co-workers also developed an alternative catalytic system for the same reaction, based on an iron-cyclopentadienyl complex, [CpFe(CO)2]2 (Scheme 27) [59][60][61].…”
Section: Inter-molecular Reactions Synthesis Of Allylic Aminesmentioning
confidence: 95%
“…Following our first report, Nicholas and co-workers also developed an alternative catalytic system for the same reaction, based on an iron-cyclopentadienyl complex, [CpFe(CO)2]2 (Scheme 27) [59][60][61].…”
Section: Inter-molecular Reactions Synthesis Of Allylic Aminesmentioning
confidence: 95%
“…We recently introduced a new synthetic way to produce allyl amines, using the more readily available nitroarenes as aminating agents, under reducing conditions (CO pressure) and in the presence of Ru 3 (CO) 12 /diimine as catalyst [33][34][35][36]. Subsequently, the use of [Cp( * )Fe(CO) 2 ] 2 as catalyst [37], the photoassisted version of this reaction [38] and the use of nitrosoarenes as aminating agents [39] have been reported. On the other hand it has long been established that nitrenes or nitrene precursors, such as N-(p-toluensulfonyl)iminophenyliodinane (PhI@NTs) can add to an alkene, forming an aziridine, or insert into the allylic C-H bond, forming an allylamine [40].…”
Section: Introductionmentioning
confidence: 98%
“…1 -3 Cyclopentadienyl metal carbonyl dimers were reported to catalyze the allylic amination of olefins 4,5 and indolization of alkynes, 6,7 and the living polymerization of vinyl monomer. 8 -10 All of these applications are on the basis of the reactivities of the metal-metal bonds.…”
Section: Introductionmentioning
confidence: 99%
“…17 -26 The nature of the bridge has a remarkable effect on the metal-metal bond and its reactivity. Vollhardt and co-workers reported that in the FvRu 2 (CO) 4 system, reversible C-C, Ru-Ru and Ru-C bond-cleavage steps lead to a photochemical process that can be thermally reversed. 17,18 For the Me 2 Si-bridged bis(tetramethylcyclopentadienyl) tetracarbonyl diruthenium complex (Me 2 Si)[C 5 Me 4 Ru(CO)] 2 (µ-CO) 2 , a photochemical albeit thermally irreversible rearrangement by Si-C bond cleavage was also observed.…”
Section: Introductionmentioning
confidence: 99%